Efficient Methods for Generating Digital Charts - Koo, T. K. (The International Hydrographic Review, 2015)
Near shore hydrographic surveying conducted for engineering works require high accuracy and high throughput because the results from these surveys serve as inputs in the engineering work cycle for cost estimates, design and construction purposes. Increasingly, this engineering work cycle is driven by the integrated process of computer-aided-engineering. Hence, the traditional end product of the hydrographic survey — the paper depth chart — can no longer satisfy the digital demands of many engineering organisations. A new product —the digital database, with the digital chart as a by-product of this digital database — is therefore urgently needed. This paper explains how inexpensive microcomputerbased digital charts can be generated from conventional analogue/digital hydrographic systems.